Effect of transcranial direct current stimulation on postoperative sleep disturbance in older patients undergoing lower limb major arthroplasty: a prospective, double-blind, pilot, randomised controlled trial - Chunyan Li; Jie Yang; He Liu; Wen Tan; Song Zhang; Hongxing Zhang; Yuan Han; Mingshu Tao; Rongguang Liu; Jiaxing Fang; Dexian Chen; Qi Wei; et al. (General Psychiatry)
Background Postoperative sleep disturbance (PSD) is a common and serious postoperative complication and is associated with poor postoperative outcomes.Aims This study aimed to investigate the effect of transcranial direct current stimulation (tDCS) on PSD in older patients undergoing lower limb major arthroplasty.Methods In this prospective, double-blind, pilot, randomised, sham-controlled trial, patients 65 years and over undergoing lower limb major arthroplasty were randomly assigned to receive active tDCS (a-tDCS) or sham tDCS (s-tDCS). The primary outcomes were the objective sleep measures on postoperative nights (N) 1 and N2.Results 116 inpatients were assessed for eligibility, and a total of 92 patients were enrolled; 47 received a-tDCS and 45 received s-tDCS. tDCS improved PSD by altering the following sleep measures in the a-tDCS and s-tDCS groups; the respective comparisons were as follows: the promotion of rapid eye movement (REM) sleep time on N1 (64.5 (33.5–105.5) vs 19.0 (0.0, 45.0) min, F=20.10, p<0.001) and N2 (75.0 (36.0–120.8) vs 30.0 (1.3–59.3) min, F=12.55, p<0.001); the total sleep time on N1 (506.0 (408.0–561.0) vs 392.0 (243.0–483.5) min, F=14.13, p<0.001) and N2 (488.5 (455.5–548.5) vs 346.0 (286.5–517.5) min, F=7.36, p=0.007); the deep sleep time on N1 (130.0 (103.3–177.0) vs 42.5 (9.8–100.8) min, F=24.4, p<0.001) and N2 (103.5 (46.0–154.8) vs 57.5 (23.3–106.5) min, F=8.4, p=0.004); and the percentages of light sleep and REM sleep on N1 and N2 (p<0.05 for each). The postoperative depression and anxiety scores did not differ significantly between the two groups. No significant adverse events were reported.Conclusion In older patients undergoing lower limb major arthroplasty, a single session of anodal tDCS over the left dorsolateral prefrontal cortex showed a potentially prophylactic effect in improving postoperative short-term objective sleep measures. However, this benefit was temporary and was not maintained over time.